Consequences of social and environmental corporate responsibility practices: Managers' perception in Mozambique - Eulália Madime; Tiago Cruz Gonçalves (International Journal of Financial Studies, 2022)
The objective of this paper is to analyze the relationship between the social and environmental practices of Corporate Social Responsibility (CSR), and the economic-financial, social, and environmental performance in Mozambican companies, from the managers' perspectives. The data were collected from a sample of 227 companies through a survey questionnaire. We used structural equation modelling to analyze how the managers correlate the different social and environmental practices with performance at the financial, social, and environmental levels. The results showed that the relationship between all major components of the social and environmental practices, and the economic-financial, social, and environmental performance is positive but insignificant with the exception of the social practices of community support, which has a weak relationship with the economic-financial performance, environmental performance, and social performance, as well as the environmental practices. The data indicate that there is a need for strengthening the appropriate economic-financial incentive policies and strategies for the agents who promote good CSR practices in the country, in order to obtain satisfactory, measurable, and comparable economic-financial, social, and environmental performance.
Keywords: 330; corporate social responsibility; economic-financial performance; environmental performance; environmental practices; social performance; social practices